One‐Pot Alkynylation of Azaaryl Aldehydes and Spontaneous Base‐Free Rearrangement into Enone Esters: an Autoinductive Mechanism. Issue 12 (30th March 2018) - Sieng, Bora; Maldonado, Matias Funes; Romagnoli, Carlo; Amedjkouh, Mohamed
Abstract : A direct synthesis of γ‐oxo‐α, β‐unsaturated esters has been developed. When heteroaromatic aldehydes are reacted with deprotonated ethyl propiolate, in the presence of Me2 Zn or BuLi, the newly formed propargylic alcohol rearranged spontaneously to give the corresponding unsaturated keto ester. Isotope labeling, allenol intermediate trapping and crossover experiments provided insight into the reactive sequence and suggest an autocatalytic mechanism. Abstract : Spontaneous rearrangement of heteroaromatic alkynols into enones involves an autocatalytic mechanism.